Firm Life Cycle, Book-Tax Differences and Earnings Persistence - Antonio Lopo Martinez; Márcio Bassetti (Revista de Educação e Pesquisa em Contabilidade, 2016)
The objective in this study is to show if the life cycle explains the relation between the Book-Tax Differences (BTDs) and earnings persistence, as well as to inform on the future gains and their relation with the BTDs. Therefore, univariate tests were applied to verify the differences between the mean BTDS, life cycle stages and regression coefficient for the Earnings Before Income Tax (EBIT). The study focused on Brazilian publicly traded companies between 2009 and 2013. The results indicated that the control of earnings persistence was related with the stages of the life cycle. The information relevance of the life cycle and the Book-Tax Differences for earnings persistence is registered. In conclusion, the firm life cycle should be included in the analysis of the relation between the BTDs and earnings persistence. The evidence registered here is crucial to identify the quality of the earnings and incorporate them into earnings valuation models.